Pengaruh Keharmonisan Keluarga Dan Dukungan Sosial Guru Terhadap Minat Belajar Peserta Didik - Muhammad Farid; Muwahidah Nurhasanah; Zumaroh (Arsy : Jurnal Studi Islam, 2022)
The study aims to know if there is or isn't a significant influence between family harmony and teacher social support of interest and learning class I mentors in MI Madinatul Ulum Mojokrapak Tembelang Jombang. The study is a quantitative study that emphasizes analysis on data-numerical data or numbers. Data analysis uses descriptive statistical analysis with data collection through angket, and documentation and random sampling techniques. This research sample is 40 first-class students in the Madinatul Ulum. Which, in turn, data were processed with test t and test f using the help of the SPSS 19 application. The results of this statistical calculation mean that an independent variable ability to explain the variability of dependencies by 76.8%, while the rest by 23.2% (100-76.8%) is defined by other factors beyond the analyzed regression model. With significant figures discovered, the research hypothesis reads there is a fairly significant influence between the variables of family harmony and the teacher's social support of student learning interests, thereby acceptable or provable hypotheses.